2013
DOI: 10.1002/14651858.cd010292
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and noradrenaline reuptake inhibitors (SNRIs) for fibromyalgia syndrome

Abstract: Arnold 2010a {published data only}Arnold LM, Clauw D, Wang F, Ahl J, Gaynor PJ, Wohlreich MM. Flexible dosed duloxetine in the treatment of fibromyalgia: a randomized, double-blind, placebocontrolled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 59 publications
1
87
0
4
Order By: Relevance
“…40 Moreover, the acupuncture treatment described in this study was associated with a lower rate of adverse effects than drug treatments used in clinical practice.…”
Section: Comparison With Previous Studies Of Pharmacological Treatmentmentioning
confidence: 74%
“…40 Moreover, the acupuncture treatment described in this study was associated with a lower rate of adverse effects than drug treatments used in clinical practice.…”
Section: Comparison With Previous Studies Of Pharmacological Treatmentmentioning
confidence: 74%
“…The regulation of pain in FMS via drug interventional studies designed to inhibit selective serotonin (SSRI) or serotonin/noradrenaline-norepinephrine (SNRI) reuptake has also resulted in the development of paroxetine, duloxetine and milnaciprin, respectively for the treatment of FMS [31]. However, despite these developments in identifying novel drug targets based on pharmacotherapeutic interventions for FMS [32], a recent analysis indicated that FMS essentially remains without effective treatments as indicated by the fact that clinical trials with tricyclic antidepressants, SSRIs, opioids, gabapentin [33] or SNRIs [34] have all produced mixed clinical efficacy results.…”
Section: Updating the Pain Pathways Relevant To Fibromyalgia: Do Theymentioning
confidence: 99%
“…Developing and coordinating evidence-based national guidelines on topics relevant to psychosomatic medicine, such as functional/somatoform or eating disorders, has been an important undertaking in recent years [22,40,41,42,43,44]. Researchers of psychosomatic medicine have also participated in several population-based cohorts in Germany (e.g.…”
Section: Psychosomatic Medicine In Academic Teaching and Researchmentioning
confidence: 99%